The design of business and safety model in oil distribution depot (Implementation: Real time strategy of simulation game) - Prasetyo, Y. Adam (2010)
Learning method for training continues to grow together with the development of technology. One of the methods is the use of games as a training employees medium. The use of games for education will be an effective method for training new employees. The characteristic of game is as a simulation for simulating the real system. The simulation system will be related to modelling system. The main purpose of the research is to get the integrated business and safety model in oil distribution depot for simulation modet. The making of business and safety model needs an intensive research to get an integrated model. So, the developed method must be got from the real system. The research methodology is simulation modelling. The model has implemented in real time strategy game simulation. Researcher has conducted research to produce a business and safety model in Oil Distribution Depot. The model has been validated using focus group method by the competent experts. The result of research shows that the designed model is good and eligible to represent business and safety in the Oil Distribution Depot system significantly. The implementation of this model could be used for model of training simulation game. This model can be use to give understanding for user who playing this simulation game about business and safety simultaneous and the interaction between them. Future research will be develop the model more detail and implementation model for different sectors.